New world, new tourism, new destinations: Implications for emerging economies and lessons for "old" tourism‐dependent developing economies. (2014) - ,
Abstract : Purpose – This paper aims to examine the position of tourism in tourism dependent countries in light of newly industrialized countries and how trends in the industry impact these developing tourism dependent nations. International tourism, for example, is now a technologically advanced activity in which some developing countries are lagging behind. These developing countries are challenged in adapting to compatible and new technology, financing, staff training and the relevant to the future of the industry.Design/methodology/approach – The study employed a qualitative research methodology using both primary and secondary data drawn from a study conducted on the South Coast of Jamaica with supporting literature from a global perspective.Findings – Moves by major players in the international tourism industry to increase their influence and dominance of global markets may reduce consumer choice thereby creating a shift for tourism from old tourism dependent developing nations to newly industrialized countries of the world. This would mean that the old tourism dependent nations need to devise a new way of diversifying their tourism products to attract elite markets seeking clean and un‐spoilt environments and destinations.Originality/value – This paper is part of a PhD work, which has been published in a book. The key issues raised in the paper are still current and the challenges present now need government and policy makers' attention.